1996
DOI: 10.1128/jcm.34.6.1407-1411.1996
|View full text |Cite
|
Sign up to set email alerts
|

Utility of PCR in diagnosing pulmonary tuberculosis

Abstract: At present, the rapid diagnosis of pulmonary tuberculosis rests with microscopy. However, this technique is insensitive and many cases of pulmonary tuberculosis cannot be initially confirmed. Nucleic acid amplification techniques are extremely sensitive, but when they are applied to tuberculosis diagnosis, they have given variable results. Investigators at six centers in Europe compared a standardized PCR system (Amplicor; Roche) against conventional culture methods. Defined clinical information was collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 23 publications
1
23
0
5
Order By: Relevance
“…Another reason for this observation could be that the sensitivity of the culture system used in our institution is lower than PCR, as reported previously. [33][34][35][36] Also, when culture is used as the gold standard test, specimens containing non-cultivable organisms may lead to a positive PCR and be considered as false-positive result. 37,38 To support the hypothesis that PCR is more sensitive than culture, it would be useful to have 2 or more positive PCR results in patients with negative cultures, 36 16 demonstrated that the yield of PCR test increased with the greater number of IS samples that were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for this observation could be that the sensitivity of the culture system used in our institution is lower than PCR, as reported previously. [33][34][35][36] Also, when culture is used as the gold standard test, specimens containing non-cultivable organisms may lead to a positive PCR and be considered as false-positive result. 37,38 To support the hypothesis that PCR is more sensitive than culture, it would be useful to have 2 or more positive PCR results in patients with negative cultures, 36 16 demonstrated that the yield of PCR test increased with the greater number of IS samples that were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For smear-negative specimens, most published studies report a sensitivity of around 60% or even less, depending on the number of samples and experiment conditions (3,4,7,9,13,16,18,20,24). This low sensitivity for smear-negative specimens shows that current amplification assays may be unsuitable in replacing cultures for the diagnosis of tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is the most rapid and economic method for detecting mycobacteria. However, given that half of the new cases of TB are smear negative, many diagnoses can not be confirmed at the time of presentation (3). This leads to delays in initiating appropriate treatment and/or the use of invasive procedures to firmly establish the diagnosis.…”
mentioning
confidence: 99%
“…Molecular techniques such as PCR and other nucleic acid amplification techniques (NAAT) are capable of detecting and identifying mycobacteria in a few hours. The sensitivities of these NAAT when applied to direct clinical specimen testing have been found to be higher than that of microscopic examination but somewhat lower than that of conventional culture methodology (3,8,19). The cost-effectiveness of performing NAAT on smearpositive specimens seems justifiable since therapeutic and isolation issues can be resolved in a timely manner.…”
Section: Discussionmentioning
confidence: 99%